2021
DOI: 10.1007/s10902-021-00466-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Differences Between Employed and Unemployed in Life Satisfaction and Emotional Well-being

Abstract: Previous research has shown that the unemployed has lower life satisfaction than the employed but that their emotional well-being may not differ. The aim is to investigate the role of mediators with bearings on these differences between the employed and unemployed in emotional well-being compared to life satisfaction. Participants were 3,463 employed and 452 unemployed living in five Western countries. They answered questions in an online survey. The results showed that the employed had both higher life satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…10 This is in line with existing literature which shows that financial circumstances are a mediator of the effect of unemployment on well-being (e.g. Dolan et al, 2008;Fors Connolly & Gärling, 2022) and on depression (e.g. Price et al, 2002;Crowe & Butterworth, 2016) because being out of work reduces income which in turn contributes to lower well-being.…”
Section: Labour Market Outcomes and Life Satisfaction (I) Overall Rel...supporting
confidence: 80%
“…10 This is in line with existing literature which shows that financial circumstances are a mediator of the effect of unemployment on well-being (e.g. Dolan et al, 2008;Fors Connolly & Gärling, 2022) and on depression (e.g. Price et al, 2002;Crowe & Butterworth, 2016) because being out of work reduces income which in turn contributes to lower well-being.…”
Section: Labour Market Outcomes and Life Satisfaction (I) Overall Rel...supporting
confidence: 80%
“…For example, papers which based their conclusions on the comparison of simple unconditional means for the treated and the untreated individuals or on path modelling (see e.g. Schwarzer et al, 1994;Lai et al, 1997;Taris, 2002;Houssemand and Meyers, 2011;Fors Connolly and Gärling, 2022).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Building on the latent deprivation model, our analyses also point to the latent functions of perceived control (mastery), meaning-making (religious struggles), and physiological restoration (sleep disturbance). Following Pearlin's stress process framework (Pearlin 1989;Pearlin et al 1981Pearlin et al , 2005Pearlin and Skaff 1996), our mediation model moved beyond the typical comparison of manifest and latent functions to better understand how pandemic job separation might undermine mental health through processes related to stress proliferation (secondary stressors) and psychosocial adaptation (secondary pathways) (Bijlsma et al 2017;Connolly and Gärling 2022;Price, Choi, and Vinokur 2002). Instead of focusing on the "relative importance" of manifest and latent functions, our research suggests that future research should focus more on "chains of adversity" and the complex relationships between financial and social psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the manifest functions of employment, numerous studies have shown substantial mediation of the association between unemployment and mental health through the loss of financial resources and the experience of financial strain (Bijlsma et al 2017; Connolly and Gärling 2022; Crowe and Butterworth 2016; de Miquel et al 2022; Frese and Mohr 1987; Kessler, House, and Turner 1987; Kessler, Turner, and House 1987, 1988; Kokko and Pulkkinen 1998; Pearlin et al 1981; Price, Choi, and Vinokur 2002; Rhee, Barak, and Gallo 2016; Wilson et al 2020; Selenko, Batinic, and Paul 2011; Thomas, Benzeval, and Stansfeld 2005; Zechmann and Paul 2019). Consistent with the latent functions of employment, researchers have also confirmed mechanisms related to structured activities and the routinization of life (e.g., keeping plans and appointments), social activity and social integration (e.g., social relationships and social support), collective purpose (e.g., contributing to community and society), feeling valued and respected (e.g., self-esteem), and keeping busy and avoiding boredom (Álvaro et al 2019; Bijlsma et al 2017; Connolly and Gärling 2022; Hoare and Machin 2010; Kokko and Pulkkinen 1998; Paul and Batinic 2010; Pearlin et al 1981; Perreault et al 2017; Selenko, Batinic, and Paul 2011; Zechmann and Paul 2019). There is even some evidence to suggest that unemployment might also contribute to poorer mental health by proliferating new stressful life events (e.g., foreclosures), undermining mastery (instilling a sense of powerlessness), and contributing to risky coping strategies like substance misuse (Kessler, Turner, and House 1987, 1988; Pearlin et al 1981; Perreault et al 2017; Price, Choi, and Vinokur 2002; Zechmann and Paul 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation